TOURISTS' INTEREST IN VISITING OPTIMALISASI PROMOSI PARIWISATA MELALUI EMOTIONAL MARKETING: PENGARUH STORYTELLING DAN STIMULUS VISUAL–AUDIO TERHADAP MINAT BERKUNJUNG WISATAWAN - Abdul Hafiz; Novita Herlissha (Journal of Economic, Bussines and Accounting (COSTING), 2025)
Tourism promotion plays a strategic role in enhancing destination competitiveness, particularly in regions with strong natural and cultural potential such as Bangka Belitung Province. This study aims to examine the influence of emotional-based tourism promotion that integrates storytelling and visual–audio stimuli on tourists’ visiting intention. This study employs a quantitative approach using a survey method involving tourists who have been exposed to Bangka Belitung tourism promotional content. Data were analyzed using a structural modeling approach to examine the relationships among the research variables. The findings indicate that emotional-based tourism promotion plays a crucial role in shaping tourists’ interest and visiting intention through emotional engagement generated by narrative elements and harmonious visual and audio presentation.These findings highlight the relevance of emotional marketing as an effective strategy in destination promotion. This study contributes theoretically to the development of emotional marketing research in the tourism context and provides practical implications for tourism stakeholders in designing more engaging, persuasive, and sustainable promotional strategies.